Penerapan Restorative Justice Dalam Perkara Penyalahgunaan Narkotika Berbasis Hukum Progresif - Affan, Ibnu; Rahmadani, Gema (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2023)
The restorative justice approach through rehabilitation in narcotics abuse cases in Indonesia is important because apart from being able to recover addicts from their dependence on narcotics, it can also overcome the problem of overcrowding in prisons.According to data from the Directorate General of Pas on May 9 2022, the number of convicts and detainees throughout Indonesia reached 273,982 people. Meanwhile, the ideal capacity of prisons and detention centers is only able to accommodate around 124,696 prisoners and detainees. Nearly 60% (sixty percent) of prison inmates are narcotics related and more than 80% (eighty percent) of that number are narcotics abusers. Keyword : Restorative Justice, Abuse, Narcotics, Progressive Law